Stability Test on Formulation of Roll on Deodorant of Lemongrass Leaf Extract (Cymbopogon citratus) - Yulia Kristyanti; Evanisia More (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Body odor is one of the health problems that can occur due to a lack of body hygiene and bacterial contamination that can decompose sweat causes body odor and unpleasant odors. Staphylococcus aureus bacteria is one of the bacteria on the skin that can decompose sweat so that it produces compounds that cause body odor. Cosmetics used to reduce or eliminate body odor are deodorants. The lemongrass plant (Cymbopogon citratus) is a plant that has a fresh aroma like lemon and has antibacterial abilities because it contains alkaloid compounds, flavonoids, tannins, terpenoids, and saponins that have antibacterial abilities. The purpose of this study was to determine the physical properties of deodorant preparations rolled on lemongrass leaf extract concentrations of 30%, 40%, and 50%. This research method is an experimental method consisting of four concentration preparations. The study results showed that the roll-on deodorant preparation of lemongrass leaf extract with concentrations of 30%, 40%, and 50% had good physical properties of the preparation.